Legal framework for training future naval infantry units officers using information and communication technologies - Zaitsev, Ihor; Kryshchuk, Bogdan (Journal of Education, Health and Sport, 2020)
The generalizatin of the statesments of normative legal acts on the implementation of the tasks of informatization of the educational process, in particular, the use of information and communication technologies in the training of future naval infantry units officer is an urgent nessecity nowadays. The development and justification of organizational, legal, economic, financial, scientific and technical, methodological bases for organizing the educational process is one of the urgent tasks of creating legislation in the field of introduction of information and communication technologies in the educational process of higher educational institutions, including higher military educational institutions. The analysis of the current normative documents on the training of future officers in higher military educational institutions will give an opportynity to improve qualitatively the effectiveness of the educational process of training future naval infantry units officers.